Analisis Kesenjangan Antara Kinerja dan Kepuasan Pasien pada Instalasi Farmasi Puskesmas Pagesangan Tahun 2017 - Hartawan, I Made Putu Sudiartha; Lesmana, Januari; Putra, I Gusti Lanang (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
Patient visits and average patient admission per year at Pagesangan Puskesmas Lombok Nusa Tenggara Barat in 2014 was 45,647 patients and decreased by 2015 ie 40,973 patients. This decrease is due to the many complaints patients have about unsatisfactory pharmaceutical services. This study aims to determine the level of patient satisfaction with pharmaceutical services in Puskesmas. This research is a descriptive research where data collection is cross sectional. The population in this study were all patients who received pharmaceutical service at Pagesangan Puskesmas Lombok Nusa Tenggara Barat in 2016 as much as 3.609 people, with the number of samples counted 98 people with accidental sampling technique (accidental). The result showed that all the average value of performance was lower than the average expectation. The pharmaceutical service indicators that need to be improved are: giving medicines information to patients, providing separate containers for different drugs, and friendly and polite service. Indicators of pharmaceutical services that need to be maintained include: Cleanliness patient waiting room at pharmacy, comfort patient waiting room at pharmacy, availability of health information (brochure, poster, etc.) in patient waiting room at pharmacy, Providing fast service, and Certainty receiving medication is the patient or the patient's family. Pharmaceutical service indicators that have not yet been repaired for performance include: tidy patient waiting room at the pharmacy, puncturing time pharmacy, pharmacy closing time, calling and ensuring patient serial number, and providing quick response to patient complaints. Indicators of pharmaceutical services that need to be prioritized for their performance include: appropriateness of placement of the signboards, cleanliness and sanitation of pharmacists, providing information to patients about the length of drug preparation, providing information in understandable languages, providing services regardless of social status, and re-asking an explanation has been given.